Ethnomathematics Exploration in Bamboo Tray Weaving (Pattapi) - Ja'faruddin, Ja'faruddin; Sitandi , Flora Frisilia; Musyawir, Musyawir; Mutmainnah , Nadia; Pratiwi, Nur Hikmah Kanzha; Syam , Delia Mustika (Jurusan Matematika FMIPA UNM, 2024)
This study aims to examine the relationship between mathematics and traditional crafts through a case study of bamboo weaving, specifically patappi or tampah. Using a qualitative case study approach, the research identifies numerical patterns and mathematical modeling inherent in the structure of bamboo weaving. Data were collected through direct observation, visual documentation, and literature review, then analyzed using number pattern concepts and mathematical functions to understand the complex geometric structure within the weaving patterns. The results indicate that the bamboo weaving pattern contains organized geometric structures, such as arithmetic sequences and Pascal’s triangle, reflecting mathematical regularity. Additionally, this study measures the tampah's capacity for filtering rice based on its size and rice density. These findings enrich understanding of the interaction between culture and science and highlight the importance of ethnomathematics in preserving local culture. Keywords: ethnomathematics; arithmetic; number patter; mathematical modeling; culture.